Home invasive mechanical ventilation in Finland in 2015-2019 - Kotanen P; Kreivi HR; Vainionpää A; Laaksovirta H; Brander P; Siirala W (European Respiratory Society, 2022)
Introduction: The prevalence of long-term invasive mechanical ventilation via tracheostomy in chronic respiratory insufficiency is largely unknown. We aimed to clarify prevalence and aetiology of the use of home invasive mechanical ventilation (HIMV) in Finland in 2015-2019.Methods: Information on HIMV patients was collected yearly from all Finnish Hospital District patient registries between 1 January 2015 and 1 January 2019. Data included underlying diagnosis, time from diagnosis to HIMV initiation, treatment length, mortality and basic sociodemographic data.Results: In 2015, we had 107 HIMV patients. During the follow-up we received 34 new patients (24.1%) and 46 patients (32.6%) died. In 2019, we had 95 HIMV patients and the prevalence in Finland was 2.0 in 100 000. The most common diagnoses were motor neurone disease (29.1%) and spinal cord injuries (19.9%). Mean duration of HIMV among all patients on 1 January 2019 was 12.3 years and among deceased patients, 11.2 years. Treatment durations ranged from 7.7 years for motor neurone disease patients to 47.3 years for post-polio syndrome patients. Most patients (81.6%) used HIMV 24 h.day(-1).Conclusions: HIMV is a rare, long-lasting treatment, most often used in chronic hypoventilation caused by chronic neurological disease. Based on our 4 year follow-up the prevalence of HIMV seems to be diminishing in Finland. Treatment duration and survival vary greatly depending on the underlying diagnosis. Most of the patients were totally dependent on HIMV, requiring 24-h care.